Restricted and unrestricted sleep schedules of Asian adolescent, high-level student athletes: effects on sleep durations, marksmanship and cognitive performance. Issue 4 (3rd July 2016) - Suppiah, Haresh T.; Low, Chee Yong; Choong, Gabriel Chee Wei; Chia, Michael
Abstract: The present study sought to compare the effects of a restricted and unrestricted sleep schedule on shooting, cognitive performance and measures of sleepiness and fatigue of Asian, adolescent high-level student athletes. Twenty-four (12 female; 14.1 ± 1.4 years) athletes performed assessments of shooting and cognitive performance (psychomotor vigilance and working memory) at the start and end of five-day restricted or unrestricted sleep (two conditions). Restricted sleep during a five-day training week resulted in no significant performance changes in cognitive or shooting performance compared with unrestricted sleep during a five-day training week, despite there being moderate-to-strong associations between increases in total sleep time and certain aspects of shooting performance. Daytime fatigue levels during the unrestricted sleep period were significantly lower than during sleep restriction. These findings highlight the relationships between nocturnal sleep extension and shooting performance amongst high-level athletes.